Resonance production in Pomeron-Pomeron collisions at the LHC - Fiore, Roberto; Jenkovszky, László; Schicker, Rainer (The European physical journal. C, Particles and fields, 2016)
A Regge pole model for Pomeron-Pomeron total cross section in the resonance region $$\sqrt{M^2}\le $$M2≤5 GeV is presented. The cross section is saturated by direct-channel contributions from the Pomeron as well as from two different f trajectories, accompanied by the isolated $$f_0(500)$$f0(500)resonance dominating the $$\sqrt{M^{2}}\le 1$$M2≤1GeV region. A slowly varying background is taken into account. The calculated Pomeron-Pomeron total cross section cannot be measured directly, but is an essential part of central diffractive processes. In preparation of future calculations of central resonance production at the hadron level, and corresponding measurements at the LHC, we normalize the Pomeron-Pomeron cross section at large masses $$σ _{t}^{PP} (\sqrt{M^2}→ ∞ ) ≈ $$σtPP(M2→∞)≈1 mb as suggested by QCD-motivated estimates.